Deep Learning Based Processing of EEG Signals for Detection and Recognition of Alzheimer Disease - Türeli, Uğur Aydın (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The aim of this study is to provide early diagnosis of Alzheimer's disease (AD). Twodimensional color image transformations of EEG signals will be processed for early diagnosis. Alzheimer's disease; It is a common type of dementia neurological disease that occurs in advanced ages and causes a decrease in thought, memory and behavioral functions. There is no definitive cure for Alzheimer's disease. However, it is possible to both slow down the process and reduce the severity of some symptoms. For this, early and accurate diagnosis is of great importance. EEG data were obtained from the dataset of 88 participants (35 healthy people, 31 with mild Alzheimer's disease and 22 with Alzheimer's disease) Alzheimer's disease and healthy people. EEG signals converted to Gramian Summation Angular Field images were firstly processed through various preprocessing steps. The 2D color image data obtained was trained and tested using the AlexNet deep learning model. AlexNet, a Convolutional Neural Network model, consists of 8 layers. In the literature review, 16 channels were selected in various studies and the 3 channels with the highest results were used. The same channels were also selected for this study. Among these channels, F7, T3 and T5 channels have the highest success rate. The three channels with the highest results were used in this study. GASF images of selected F7, T3 and T5 channels were used to train the AlexNet CNN model over 50 epochs. The developed model achieved promising performance with 98.03% accuracy, 98.21% sensitivity and 97.84% specificity. In addition, the AlexNet CNN model was trained and tested over 50 epochs with 4-fold Cross Validation. As a result of this study, the developed model achieved the highest results with 98.02% accuracy, 98.01% sensitivity and 98.04% specificity

ÖZ: Bu çalışmanın amacı Alzheimer hastalığının (AD) erken teşhisini sağlamaktır. Erken teşhis için EEG sinyallerini iki boyutlu renkli görüntü dönüşümleri işlenecektir. Alzheimer hastalığı; düşünce, hafıza ve davranış fonksiyonlarında azalmaya neden olan ve ileri yaşlarda ortaya çıkan yaygın olarak görülen bir demasn türü nörolojik bir hastalıktır. Alzheimer hastalığının kesin bir tedavisi yoktur. Fakat hem süreci yavaşlatmak hem de kimi belirtilerin şiddetini azaltmak mümkündür. Bunun için de erken ve doğru tanı büyük önem taşır. EEG verileri, Alzheimer hastalığı olan ve sağlıklı olan 88 katılımcının (35 sağlıklı, 31 hafif Alzheimer hastalığı ve 22 Alzheimer hastalığı) veri setinden elde edildi. Gramian Summation Angular Field görüntülerine dönüştürülen EEG sinyalleri öncelikle çeşitli ön işleme adımlarından geçirilmiştir. Elde edilen 2B renkli görüntü verilerini AlexNet derin öğrenme modeli kullanılarak eğitilmiş ve test edilmiştir. Evrişimsel Sinir Ağı modeli olan AlexNet 8 katmandan oluşur. Literatür taramasında çeşitli çalışmalarda 16 kanal seçilmiş ve en yüksek sonuç veren 3 kanal kullanılmıştır. Aynı kanallar bu çalışma için de seçilmiştir. Bu kanallar ara sında F7, T3 ve T5 kanalları başarı oranı en yüksek olan kanallardır. bu çalışmada en yüksek sonuç veren üç kanal kullanılmıştır. Seçilen F7, T3, T5 kanallarının GASF görüntüleri, AlexNet CNN modelini 50 dönemin üzerinde eğitmek için kullanıldı. Geliştirilen model %98,03 doğruluk, %98,21 duyarlılık ve %97,84 özgüllük ile umut verici bir performans elde etmiştir. Ek olarak, AlexNet CNN modeli 4-kat Çapraz Doğrulama ile 50 dönemin üzerinde eğitildi ve test edildi. Bu çalışma sonucunda geliştirilen model %98,02 doğruluk, %98,01 duyarlılık ve %98.04 özgüllük ile en yüksek sonuçlara ulaşmıştır.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2023. Supervisor: Assoc. Prof. Dr. Adnan Acan.
Keywords: Thesis Tez; Computer Engineering Department; Artificial intelligence--Medical applications; Medical informatics; Biomedical engineering; Artificial Intelligence--Medical Applications; Artificial Intelligence--Computational intelligence; Alzheimer disease; deep learning; eeg; gasf; cnn